A highly efficient purely organic room-temperature phosphorescence film based on a selenium-containing emitter for sensitive oxygen detection. Issue 31 (19th July 2021) - Wang, Shuai; Shu, Haiyang; Han, Xianchao; Wu, Xiaofu; Tong, Hui; Wang, Lixiang
Abstract : A purely organic room-temperature phosphorescence emitter based on 9 H -selenoxanthen-9-one achieves a high phosphorescence quantum yield of 44.3% in doped films, and highly reversible and sensitive oxygen-sensing performance. Abstract : Developing purely organic room-temperature phosphorescence (RTP) materials with high phosphorescence efficiency in film states is important for their applications but remains a great challenge. Herein, a donor–acceptor type RTP molecule (SeX-CzPh ) with 9 H -selenoxanthen-9-one and 9-phenyl-9 H -carbazole as the acceptor and donor units, respectively, is designed and synthesized. SeX-CzPh shows a high phosphorescence quantum yield of 44.3% in a doped polystyrene film at room temperature, which is 4-fold higher than that of its analogue TX-CzPh with 9 H -thioxanthene-9-one as the acceptor unit. The heavy selenium atom plays a key role in achieving high phosphorescence quantum yields, owing to the effective ISC process through strong spin–orbit coupling. Moreover, the SeX-CzPh -based oxygen film sensor exhibits a wide detection range (0–2.1 × 10 5 ppm), a high K SV (1.27 × 10 −4 ppm −1 ) and a low detection limit (4.9 ppm). This work demonstrates that 9 H -selenoxanthen-9-one is a promising building block for the rational design of highly efficient purely organic RTP materials.